Enhancing the production of volatile fatty acids by potassium permanganate from wasted sewage sludge: A batch test experiment - Antonio Mineo; Alida Cosenza; Bing-Jie Ni; Giorgio Mannina (Heliyon, 2023)
Recovering resources from wastewater treatment is vital for the transition from a linear to a circular economy model in the water sector. Volatile Fatty Acids (VFAs) are valuable products among the possible recovered resources. This study investigates the influence of potassium permanganate (KMnO4) addition during acidogenic fermentation of waste activated sludge for enhancing VFAs production. Specifically, different fermentation batch tests with and without KMnO4 addition were carried out using two distinctive sewage sludges as feedstocks. Results showed that KMnO4 addition increased the VFAs yield up to 144 and 196 mgCOD/g VSS for the two sludges. When KMnO4 was used as pre-treatment, 55 % of sCOD were VFAs. This latter result was mainly debited to the recalcitrant organics’ disruption promoted by the oxidative permanganate ability.